An Investigation of Students’ Strategies and Methods in Translating English Text into Indonesian - Yudhie Indra G; Aris Setiawan (Journal of English Language Studies, 2017)
English has important function in every aspect in this era, especially in education side. Someone demanded to know the meaning and function of English word. So that, translation is also the other four skills in mastering English language, besides Listening, Speaking, Reading, and Writing, Translation is also has main function. The objectives of this research were to find out if the students commit translation in English Text, to describe the method which was applied by the students to translate the English text, to observe the students ability in translate the English text. Therefore, this study seemed very relevant to a case study because it attempted to investigate and explore the student’s strategies in one class of 23 students. In this research, the researcher applied test to the students. In technique of the test, the researcher gave the English text and asked the students to translated the English text as well as possible as they could. There are four criteria to assess the student’s translation, they are message content accuracy, message distinct, equivalences of using language and the last are mechanic appropriateness. The researcher also has done interviewed the translation lecturer regarded as the key of the informant who really knew how far the student’s ability to translate English text. The result of the interview was given to the teacher; showed 4th semester students still got lot of difficulties, they only used one technique in translate. Especially the words seldom their finds in the English lesson books. Furthermore, the lecturer should be creative by finding the appropriate method of translation for 4th semester students in translating English text into Indonesian language, and the lecturer also gives always motivation to the students that the text must understand with translate the source language into their target language exactly in Indonesian language. Meanwhile the students also needed longer time to practice in translating text from English text into Indonesian text because they don’t have right method and also lack of vocabulary in translating English text although the lecturer had already given exercise to practice of English text, but it was not enough to build students interest to practice translating English text.Keywords:  Translation; Students Translation Strategies and Method; Indonesian Text